2010
DOI: 10.1007/s11270-010-0581-z
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Mercury Associated with Different Phytoplankton Size Fractions in Lahontan Reservoir, Nevada

Abstract: Sampling is conducted during 2006 in Lahontan Reservoir, Nevada to investigate seasonal variation of total mercury (THg) and methylmercury (MeHg) partitioning in different phytoplankton size fractions as a function of point source (fluvial) mercury (Hg) loads, reservoir residence time, and algal growth. Carson River Hg inputs into the reservoir are extremely dynamic with spring loads two orders of magnitude larger than summer loads. Chlorophyll a measurements show two periods of algal growth. A small amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Overall results suggest the predominance of nano‐ and pico‐phytoplankton over micro‐phytoplankton would lead to heavy MeHg accumulation in planktonic and planktivorous communities. While this hypothesis has not been tested with seawater, Carroll et al () reported that particle–water partition coefficients for MeHg and biomass MeHg concentrations were greater for smaller particles than larger ones in a freshwater reservoir, indicating that small and more palatable phytoplankton are important mediators for MeHg transfer to higher trophic organisms. Various environmental factors, such as nutrient input rate, water residence time, mixed layer depth, and light intensity, are known to affect the cell‐size distribution of the phytoplankton community in seawater (Parsons and Takahash,; Thomas et al,).…”
Section: Resultsmentioning
confidence: 99%
“…Overall results suggest the predominance of nano‐ and pico‐phytoplankton over micro‐phytoplankton would lead to heavy MeHg accumulation in planktonic and planktivorous communities. While this hypothesis has not been tested with seawater, Carroll et al () reported that particle–water partition coefficients for MeHg and biomass MeHg concentrations were greater for smaller particles than larger ones in a freshwater reservoir, indicating that small and more palatable phytoplankton are important mediators for MeHg transfer to higher trophic organisms. Various environmental factors, such as nutrient input rate, water residence time, mixed layer depth, and light intensity, are known to affect the cell‐size distribution of the phytoplankton community in seawater (Parsons and Takahash,; Thomas et al,).…”
Section: Resultsmentioning
confidence: 99%
“…High phytoplanktonic Hg content can be found in contaminated areas, notably those impacted by metal mining . In the Carson River–Lahontan Reservoir (NV, USA), classified as a Superfund site, phytoplankton were found to contain from 30 nmol to 254 nmol Hg g −1 dry weight and 1 nmol to 28 nmol CH 3 Hg g −1 dry weight .…”
Section: Hg Uptake By Phytoplanktonmentioning
confidence: 99%
“…High phytoplanktonic Hg content can be found in contaminated areas, notably those impacted by metal mining [88,89]. In the Carson River-Lahontan Reservoir (NV, USA), classified as a Superfund site, phytoplankton were found to contain from 30 nmol to 254 nmol Hg g À1 dry weight and 1 nmol to 28 nmol CH 3 Hg g À1 dry weight [90]. Although these accumulation values are useful for assessing the extent of Hg contamination in natural waters, they should be interpreted with care.…”
Section: Hg Accumulation By Natural Algal Communitiesmentioning
confidence: 99%
“…Additionally, transient events such as pulses of large loads are simulated to propagate through the system with attenuation over time and downstream movement; while dilution occurs near the dam with influxes from the Truckee Canal. Few data exist in the reservoir, with data collected only at FPO (Carroll et al ., ) or LDM by the USGS. All post‐flood reservoir data were collected during the summer of 2006, with data at LDM collected at three discrete depths and vertically volume‐weighted to compare with model output.…”
Section: Resultsmentioning
confidence: 99%
“…Ongoing work is looking at bioaccumulation within the reservoir and the impacts of both reducing DMeHg loading from the river on predicted response as well as decoupling the timing of DMeHg influx from peak bioenergetics (i.e., consumption) of Hg enriched phytoplankton (Carroll et al, 2011). In addition, we are currently driving the CRLR transport model with hydrologic predictions (USBR, 2011) based on 112 down-scaled climate projections from the World Climate Research Programme Coupled Model Intercomparison Project 3.…”
Section: Discussionmentioning
confidence: 99%